Applications and challenges of photodynamic therapy in the treatment of skin malignancies - Hua, Yunqi; Tian, Xiaoling; Zhang, Xinyi; Song, Ge; Liu, Yubo; Zhao, Ye; Gao, Yuqian; Yin, Fangrui (Frontiers in Pharmacology, 2024)
Photodynamic Therapy (PDT), as a minimally invasive treatment method, has demonstrated its distinct advantages in the management of skin malignant tumors. This article examines the current application status of PDT, assesses its successful cases and challenges in clinical treatment, and anticipates its future development trends. PDT utilizes photosensitizers to interact with light of specific wavelengths to generate reactive oxygen species that selectively eradicate cancer cells. Despite PDT's exceptional performance in enhancing patients' quality of life and prognosis, the limitation of treatment depth and the side effects of photosensitizers remain unresolved issues. With the advancement of novel photosensitizers and innovative treatment technology, the application prospects of PDT are increasingly expansive.This article delves into the mechanism of PDT, its application in various skin malignancies, its advantages and limitations, and envisions its future development.We believe that through continuous technological enhancements and integration with other treatment technologies, PDT has the potential to assume a more pivotal role in the treatment of skin malignancies.